1989
DOI: 10.1007/bf02458444
|View full text |Cite
|
Sign up to set email alerts
|

Memory but no suppression in low-dimensional symmetric idiotypic networks

Abstract: We present a new symmetric model of the idiotypic immune network. The model specifies clones of B-lymphocytes and incorporates: (1) influx and decay of cells; (2) symmetric stimulatory and inhibitory idiotypic interactions; (3) an explicit affinity parameter (matrix); (4) external (i.e. nonidiotypic) antigens. Suppression is the dominant interaction, i.e. strong idiotypic interactions are always suppressive. This precludes reciprocal stimulation of large clones and thus infinite proliferation. Idiotypic intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(13 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…A new class of network models has been developed by De Boer (1988), Perelson (1988Perelson ( , 1989a, Varela et al (1988), De Boer & Hogeweg (1989a, De Boer et aL (1990), and Weisbuch (1990). These models rely only upon stimulatory network interactions; a decrease in the amplitude of stimulation plays the role of suppression.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A new class of network models has been developed by De Boer (1988), Perelson (1988Perelson ( , 1989a, Varela et al (1988), De Boer & Hogeweg (1989a, De Boer et aL (1990), and Weisbuch (1990). These models rely only upon stimulatory network interactions; a decrease in the amplitude of stimulation plays the role of suppression.…”
Section: Introductionmentioning
confidence: 99%
“…The problem of immunity and the chain reaction in networks with only stimulatory interactions was analyzed by De Boer (1988) and De Boer & Hogeweg (1989a. These authors first showed that a stimulatory idiotypic interaction between an Abl and an Ab2 clone accounts for a stable immune-state in which an elevated Ab2 clone maintains the stimulation of an even larger Abl clone (De Boer, 1988;De Boer & Hogeweg, 1989a ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…de, Perelson and Delisi, 1980;used in De Boer, 1988;De Boer et al, 1989a,b, 1991Weisbuch et al, 1990;Perelson and Weisbuch, 1992) and its value gives the proportion of normal B cells or memory B cells which can be activated to differentiate into plasma cells depending on the field H. 8, and 8, are the threshold parameters at which the function approximately reaches its half-maximum, i.e. 0.5 (see Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Jerne's (1974) hypothesis that the immune system functions by means of a network of idiotypic interactions has been investigated extensively by theoretical biologists. Theoretical models that can account for memory, tolerance and repertoire selection (Hoffmann, 1980;De Boer and Hogeweg, 1989a;Weisbuch et al, 1990;De Boer and Perelson, 1991) have been developed and they have interesting self-organizing properties (De Boer and Perelson, 1991;De Boer et al, 1992aStewart and Varela, 1991).…”
mentioning
confidence: 99%